1998
DOI: 10.1007/s004250050335
|View full text |Cite
|
Sign up to set email alerts
|

Probing the "malate hypothesis" of differential aluminum tolerance in wheat by using other rhizotoxic ions as proxies for Al

Abstract: An Al-stimulated eux of malate from the root apex has been proposed as the primary mechanism whereby some wheat (Triticum aestivum L.) genotypes demonstrate marked resistance to the rhixotoxic metal Al. Appealing in its simplicity, the model has not been unequivocally validated, and suers from some signi®-cant discrepancies between estimated, steady-state concentrations of malate at the root surface and concentrations that are necessary to explain the resistance of the superior genotypes. Using two other rhizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 31 publications
2
32
1
Order By: Relevance
“…the value at which the formation of tridecamer was the most efficient, the relative root growth reached its minimum level, which clearly provides the toxicity of this Al form. Similar conclusions were drawn by Parker and Pedler (1998) from tests with maize. Other authors (Wallace 1992;Wagatsuma et al 2001) reported the toxic influence of polymeric Al forms on oat tolerant towards mono-nucleus forms.…”
Section: Polymeric Forms Of Al 13supporting
confidence: 83%
“…the value at which the formation of tridecamer was the most efficient, the relative root growth reached its minimum level, which clearly provides the toxicity of this Al form. Similar conclusions were drawn by Parker and Pedler (1998) from tests with maize. Other authors (Wallace 1992;Wagatsuma et al 2001) reported the toxic influence of polymeric Al forms on oat tolerant towards mono-nucleus forms.…”
Section: Polymeric Forms Of Al 13supporting
confidence: 83%
“…Compared with citrate and oxalate, malate is suggested to bind to Al less effectively (Hue et al, 1986). This raises a question as to whether malate efflux is insufficient to explain the Al-resistance mechanism in wheat cultivars (Parker and Pedler, 1998). To examine the possible role of malate efflux in the Al-resistance mechanism, we asked if inhibition of malate efflux by K-252a would affect Al accumulation in root apexes and on Al-induced inhibition of root growth in cv Atlas.…”
Section: Malate Efflux Confers Al Resistance In Wheatmentioning
confidence: 99%
“…Stoichiometric considerations would indeed suggest that the amount of organic acids secreted by root apices of Al resistant wheat and maize genotypes might only be adequate to detoxify Al at concentrations well below those inhibiting root growth of signalgrass (Delhaize et al, 1993;Pellet et al, 1995Pellet et al, , 1997Ryan et al, 1995b;Parker and Pedler, 1998). The effectiveness of Al resistance mechanisms based on external chelation of Al 3ϩ by chelating ligands may also be limited by other cell-surface ligands competing for Al ions (Parker and Pedler, 1998), the presence of other cations capable of forming complexes with organic acids (Jones and Darrah, 1994), adsorption of organic acids to the soil's exchange phase (Jones et al, 1996a), and rapid microbial degradation of organic acids in soils (Jones et al, 1996b). In addition, an Al exclusion mechanism based on the efflux of phosphate may be of questionable adaptive value in highly weathered acid soils where P is the principal limiting nutrient.…”
Section: External Al Detoxification Mechanisms May Not Be Efficient Ementioning
confidence: 99%